2008
DOI: 10.1016/j.neuroimage.2007.09.064
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging of individuals with Down’s syndrome at-risk for dementia: Evidence for possible compensatory events

Abstract: Background-We report functional and structural brain indicators that may precede the onset of dementia in individuals with Down syndrome (DS).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 71 publications
3
46
0
Order By: Relevance
“…This analysis detected areas of the brain in which there was overlapping significance (e.g., Haier et al, 2008). The only area to survive this analysis was the putamen.…”
Section: Resultsmentioning
confidence: 99%
“…This analysis detected areas of the brain in which there was overlapping significance (e.g., Haier et al, 2008). The only area to survive this analysis was the putamen.…”
Section: Resultsmentioning
confidence: 99%
“…While there was a close correlation between antemortem PET and postmortem histopathological measurements of Aβ plaques in this DS participant with AD dementia, florbetapir PET measurements may be less sensitive to the detection of the primarily diffuse Aβ plaques that have been reported in virtually all DS/AD- individuals who expired by the age of 35 39 .Previously published FDG PET studies have reported a pattern of CMRgl reductions in DS adults with and without AD dementia similar to that observed in late-onset AD 40 , consistent with the findings reported in our study. In addition, Haier et al, reported increased inferior and medial temporal CMRgl 11,12 in middle-aged DS/AD- participants, raising the possibility of compensatory increases in local neuronal activity in preclinical stages of AD.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, smaller brain volume has been documented in temporal areas and in the cerebellum in individuals with DS compared to healthy controls (White et al 2003;Haier et al 2008).…”
Section: Discussionmentioning
confidence: 99%